The Heads-Ed: A Brief Mental Health Screening Tool for Use in the emergency department. (1st June 2016) - Gray, C; Cloutier, P; Cappelli, M; Kennedy, A; Zemek, R
Abstract: BACKGROUND: The hospital emergency department (ED) is an important entry point for children and youth into the mental health (MH) and addicitons system. Many EDs are challenged in managing child and youth MD/addictions due to lack of clinical resources, standardized screening tools and/or training. Currently, there is no standard of practic or tool used to guide the assessment and disposition of MH concerns within the ED. In fact, researchers have found that only a small minority (<10%) of ED physicians indicate using evidence based screening methods to assess MH concerns. The American Academy of Pediatrics called for improved screening of MH issues in the ED. In response, we developed HEADS-ED, a rapid screening tool that represents Home, Education, Activities/peers, Drugs/alcohol, Suicidality, Emotions/behaviour, Discharge resources. OBJECTIVES: This presentation will summarize 3 studies completed to date examining the inter rater reliability, sensitivity & specificity of the HEADS-ED. In addition, data will be presented regarding the utility of the HEADS-ED in predicting consultation with psychiatry and admission to hospital. DESIGN/METHODS: In Study #1, Crisis Intervention Workers (CIWs) completed the HEADS-ED and the Child and Adolescent Needs and Strength tool (CANS-MH 3.0) on patients presenting to the ED with MH concerns between March 1 and May 30, 2011. In Study #2, ED physicians completed the HEADS-ED for patients presenting to the ED with MH concerns between May 5, 2013 and February 10, 2014. RESULTS: In Study #1, there were 313 participants (M=14.3 years, SD = 2.63 years, 58.1% female). Inter rater reliability analysis revealed strong agreement between raters (r=.79). The HEADS-EDitems were significantly correlated with CANS-MH 3.0 scores on related items. The HEADS-ED also predicted consultation with psychiatry and admission to hospital (sensitivity 82%, specificity 87%). In Study #2, there were 589 participants (M = 15.13 years; SD = 1.41; 72.7% female) seen by the ED physicians. The HEADS-ED predicted consultation to psychiatry/crisis team (sensitivity 92.1%, specificity 72.3%). CONCLUSION: Results provide evidence to supor the psychometric properties of the HEADS-ED. The HEADS-ED is a useful tool to standardize the language used to discuss and assess pediatric MH patients int he ED. The brief, inuitive measure has the potential to determine referral for psychiatric consultation, admission decisions and help guide selection of discharge resources.